Proposed Design Philosophy for Seismic-Resistant Buildings - Nanang Gunawan; Aylie Han; Buntara Sthenly Gan (Civil Engineering Dimension, 2019)
Modern seismic design and technologies have undergone tremendous developments. In modern design codes, building structures subjected to high earthquake loads are allowed to experience plastic deformations without collapsing, and the design is permitted up to the ultimate strength. According to comparative results in Japan, the number of humans injured due to earthquakes is higher than the number of deaths/missing. Likewise, the number of residential buildings that collapsed are less than the partially damaged buildings. This outcome implies that residential buildings designed based on the revised seismic standards have good earthquake resistances. It also infers that the human deaths/injury casualties were not a result of the collapsed the structure, but due to the strong vibrations originated from the earthquake, yielding in the collapse of non-structural elements such as ceilings and bookshelves. This paper presents a proposed design philosophy that attempts to implement the effect of earthquakes to non-fatal human casualties